Marketing Model of Halal Tourism Destination - Dian Wardiana Sjuchro; Surya Dewi; Sudarmi; Ardiansyah Goeliling; Andi Abriani (Jurnal Komunikasi Profesional, 2023)
Halal Tourism is a spirituality tourism monitored by government and marketed due to Indonesian Majority of Muslim religion invested their time and money for it. As the technology advancement occurred, it invites more visitors in Indonesia; therefore, finding marketing model is important to preserve the values of Halal Tourism in Indonesia. With qualitative content analysis, Author is able to examine the video structures ranging from visual, text, and meaning which would elaborate the essential element to be put in marketing model visualization. The analysis could build greater investment if the analysis result could influence the suggestion, and the suggestion is implemented in action. After all the Halal Tourism as spirituality tourism is also dynamic especially after COVID-19 Pandemic.